2015
DOI: 10.3109/01480545.2015.1070170
|View full text |Cite
|
Sign up to set email alerts
|

Thearubigins protect against acetaminophen-induced hepatic and renal injury in mice: biochemical, histopathological, immunohistochemical, and flow cytometry study

Abstract: Thearubigins protected against acetaminophen-induced hepatotoxicity and nephrotoxicity in mice possibly through their antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…This suggests that FA may play a protective role as an antioxidant in APAP toxicity. It is reported that different doses of APAP administration causes kidney damage such as tubular vacuolization, lymphocyte infiltration and tubular dilatation [40][41][42]. In our study, hyperemia in vessels, dilatation in tubules and disruptions in tubular epithelium were observed in APAP group.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This suggests that FA may play a protective role as an antioxidant in APAP toxicity. It is reported that different doses of APAP administration causes kidney damage such as tubular vacuolization, lymphocyte infiltration and tubular dilatation [40][41][42]. In our study, hyperemia in vessels, dilatation in tubules and disruptions in tubular epithelium were observed in APAP group.…”
Section: Discussionsupporting
confidence: 59%
“…Studies indicated that APAP causes severe liver damage such as massive neutrophilic and lymphocytic infiltration, intense coagulative necrosis, cytoplasmic vacuoles, vacuolar degeneration in hepatocytes, congestion of central vein and portal vein in the liver [23,40]. In our study, APAP group showed dilatation of the central veins, centrilobular necrosis, congestion and vacuolar degeneration, as well as loss of glycogen storage ability of hepatic parenchyma.…”
Section: Discussionsupporting
confidence: 57%
“…8, which shows large signals attributable to the A-ring methine carbons. Kuhnert reported that the molecular weights of TRs are less than 2000 Da 108) ; however, this is also still contentious, 96,112) and the discrepancy may be caused by the different extraction solvents and preparation methods that are used for preparation of TRs.…”
Section: Thearubiginsmentioning
confidence: 99%
“…Numerous studies have reported the biological activities of TRs. Murad and colleagues reported that TRs protected against acetaminophen-induced hepatotoxicity and nephrotoxicity in mice [24], and improved the sildenafil-induced delayed gut motility in mice [25]. Halder et al found that TRs have significant antimutagenic and anticlastogenic effects in Salmonella assay in vitro and in vivo in bone marrow cells of mice [26].…”
Section: Introductionmentioning
confidence: 99%